Cross-reactivity with Brazilian strains of B after immunization with outer membrane vesicles - Gabriela Trzewikoswki de Lima; Amanda Izeli Portilho; Elizabeth De Gaspari (SAGE Publishing, 2019)
Background: Immunization against Neisseria meningitidis is important for public health. Vaccines composed of cross-reactivity antigens avoid strain-specific responses, ensuring more comprehensive protection. Methods: The cross-reactivity between three strains from the last outbreak of N. meningitidis in Brazil was assessed in our studies, using enzyme-linked immunosorbent assay (ELISA) and immunoblotting assays. Results: Both assays verifed a similar humoral response between the strains evaluated. Patterns of antigen recognition differed with each dose evaluated. Conclusions: We observed that immunization with N. meningitidis B outer membrane vesicles (OMVs) led to the production of antibodies that recognized antigens of heterologous strains, indicating possible protection against these evaluated strains.